Matrix metalloproteinase-9 contributes to intestinal tumourigenesis in the adenomatous polyposis coli multiple intestinal neoplasia mouse - Sinnamon, Mark J (Blackwell Science Inc, 2008)
Matrix metalloproteinases (MMPs) are a family of 23 extracellular proteases that are best known for their collective ability to degrade all components of the extracellular matrix. We previously demonstrated that genetic ablation of MMP-7 reduced tumour multiplicity in multiple intestinal neoplasia (Min) mice possessing a genetic alteration in the adenomatous polyposis coli gene (APC). These mice, commonly referred to as APC-Min mice, are a frequently used model of early intestinal tumourigenesis. To examine further the role of MMPs in intestinal tumour development, we generated APC-Min mice genetically deficient in MMP-2, -9, -12 or -19. Genetic ablation of MMP-2, -12 or -19 did not affect multiplicity or size of intestinal tumours when crossed into the APC-Min system. However, MMP-9 deficient animals developed 40% fewer tumours than littermate controls, although tumour size distribution remained unaffected. Intestinal adenomas from MMP-9 deficient mice demonstrated a 50% decrease in proliferating cells compared with control tissues, with no difference in apoptosis. To determine the cellular origin of MMP-9 in these tumours, immunofluorescent co-staining with markers for different leucocyte lineages was used to demonstrate that intratumoural MMP-9 is largely a product of neutrophils. These studies extend the potential targets for chemoprevention of intestinal adenomas to MMP-9 in addition to MMP-7 and exclude MMP-2,-12,-19 as attractive targets for intervention.